1988
DOI: 10.1002/clc.4960110606
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and prognostic implications of a large pericardial effusion in men

Abstract: Summary:To assess the etiology and prognosis of a large pericardial effusion, we reviewed 25 consecutive patients who presented with a large pericardial effusion and underwent a drainage procedure. Large pericardial effusion was defined as: (1) an echo-free space 2 10 mm anteriorly and posteriorly by M-mode echocardiography and (2) removal of 1 350 ml of fluid at pencardial drainage. The etiologies of large pericardial effusion were: neoplastic (36%), idiopathic (32 %), uremic (20%), postmyocardial infarction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
3
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 24 publications
3
40
3
1
Order By: Relevance
“…This finding contrasts with previous clinical studies, which reported malignant diseases as the most common cause of pericardial tamponade, reaching 30-60% of cases [6][7][8][9][10][11]. This shift in tamponade etiology is apparently due to the increase in recent years in the overall number and in the complexity of percutaneous intra-cardiac procedures, as well as the introduction of interventional techniques such as trans-catheter valve replacement and catheter ablation for atrial fibrillation, all reported to be possibly complicated by cardiac tamponade [12][13][14][15].…”
Section: Discussioncontrasting
confidence: 98%
“…This finding contrasts with previous clinical studies, which reported malignant diseases as the most common cause of pericardial tamponade, reaching 30-60% of cases [6][7][8][9][10][11]. This shift in tamponade etiology is apparently due to the increase in recent years in the overall number and in the complexity of percutaneous intra-cardiac procedures, as well as the introduction of interventional techniques such as trans-catheter valve replacement and catheter ablation for atrial fibrillation, all reported to be possibly complicated by cardiac tamponade [12][13][14][15].…”
Section: Discussioncontrasting
confidence: 98%
“…In two series on large pericardial effusions tamponade was reported in 44% and 37% of patients respectively. There were no cases of pericardial rupture as a complication reported in them, the mechanism by which our patient's pericardium appears to have decompressed [2,3].…”
Section: Discussionmentioning
confidence: 64%
“…Aggressive work-up including pericardial biopsy failed to reveal a specific etiology. The patient recovered with conser- Four major studies [2][3][4][5] have addressed the investigation of large pericardial effusions of unknown etiology. In the largest of these studies, 37% of patients with moderate and severe effusion had cardiac tamponade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being a disease of protean manifestation, it poses a diagnostic dilemma to medical practioners even in endemic areas where clinical suspicion is high [1][2][3][4] . In many patients, an exclusive workup fails to identify the etiological agent.…”
Section: Introductionmentioning
confidence: 99%